2016
DOI: 10.3390/pharmaceutics8010008
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Assessments of RNA-seq by the SEQC Consortium: FDA-Led Efforts Advance Precision Medicine

Abstract: Studies on gene expression in response to therapy have led to the discovery of pharmacogenomics biomarkers and advances in precision medicine. Whole transcriptome sequencing (RNA-seq) is an emerging tool for profiling gene expression and has received wide adoption in the biomedical research community. However, its value in regulatory decision making requires rigorous assessment and consensus between various stakeholders, including the research community, regulatory agencies, and industry. The FDA-led SEquencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 19 publications
0
42
0
Order By: Relevance
“…The transcriptome, which is assessed by RNA-seq, is widely considered to be the most mature omics technology with a long measure and the greatest depth of coverage. 26,27 This approach is also advantageous when the protein products of genes are either recalcitrant to proteomic analysis or of low abundance, which can result in their under-representation in some conditions. 28 The proteomic analysis is widely used in the analyses of differential expression of proteins in order to understand the changes of protein expression between experimental and control group.…”
Section: Discussionmentioning
confidence: 99%
“…The transcriptome, which is assessed by RNA-seq, is widely considered to be the most mature omics technology with a long measure and the greatest depth of coverage. 26,27 This approach is also advantageous when the protein products of genes are either recalcitrant to proteomic analysis or of low abundance, which can result in their under-representation in some conditions. 28 The proteomic analysis is widely used in the analyses of differential expression of proteins in order to understand the changes of protein expression between experimental and control group.…”
Section: Discussionmentioning
confidence: 99%
“…The training dataset consisted of 249 samples, and the other 249 samples were in the validation/test dataset. We used the sample distribution as defined in SEQC project [4][5][6].…”
Section: Seqc Neuroblastoma Datasetmentioning
confidence: 99%
“…In general, "multi-platform" refers to data from multiple technologies or from different sites/tissues/organs, which usually have close linkages or relationships between data platforms. For example, the Sequencing Quality Control (SEQC) project [5,6] studied a large neuroblastoma cohort with both Microarray (Agilent) and RNA-seq (Illumina Hi-seq) datasets.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have found a higher than expected mutation frequency of candidate cancer genes and RNA sequencing technology has the potential to detect such abnormal regulations in the cancer [53][54][55][56]. The most typical and challenging condition with the cancer is ''Metastasis'' a term that was originally coined in 1829 by Jean Claude Recamier.…”
Section: Expression Studies On Cancer With Transcriptome Sequencingmentioning
confidence: 99%